2018
DOI: 10.1590/s1678-9946201860002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Streptococcus agalactiae colonization in pregnant women from the 18th Health Region of Paraná State

Abstract: Introduction The aim of this study was to determine the prevalence of GBS colonization in pregnant women in a public health service.Methods A study of 496 pregnant women at 35-37 gestational weeks was conducted from September 2011 to March 2014 in 21 municipalities of the 18th Health Region of Paraná State. Vaginal and anorectal samples of each woman were plated on sheep blood agar, and in HPTH and Todd-Hewitt enrichment broths.Results Of the 496 pregnant women, 141 (28.4%) were positive for GBS based on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
22
2
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 11 publications
8
22
2
8
Order By: Relevance
“…It is noteworthy that in the present study the GBS vaginal and rectal colonization rates were 4.58% and 3.33%, respectively, while concomitant rectovaginal colonization rate was reported as 1.25%. This finding was almost similar with other studies 3,7,14 and reveals that multisite swabbing may be important in identifying GBS colonization.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It is noteworthy that in the present study the GBS vaginal and rectal colonization rates were 4.58% and 3.33%, respectively, while concomitant rectovaginal colonization rate was reported as 1.25%. This finding was almost similar with other studies 3,7,14 and reveals that multisite swabbing may be important in identifying GBS colonization.…”
Section: Discussionsupporting
confidence: 92%
“…Epidemiological studies have revealed that GBS-colonized pregnant women are > 25 times more likely to deliver infants with early-onset GBS disease. 13,14 In the present study, the overall prevalence of GBS colonization among pregnant women was found to be 6.7%. This finding was slightly lower than many other reports in Iran [15][16][17] and other developing countries such as Ethiopia (7.2%), Turkey (8%), China (7.1%) and Korea (8.3%), 13,18-20 but higher than those reported in India (2.3%) and Taiwan (6.2%).…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Ao mesmo tempo, em estudo realizado Taiwan com 154.088 mulheres, a prevalência foi de 19.58% (HUNG et al, 2018), assemelhando-se a encontrada no presente artigo. Já em nível nacional, um estudo recente, com gestantes do Paraná, apresentou prevalência de 28,4% (MELO et al, 2018). Em âmbito regional, destaca-se um estudo realizado em Caxias do Sul, com 204 gestantes, estando a prevalência próxima aos valores do estudo, os quais variam de 22,5% (vaginal) a 26% (perianal) (WOLLHEIM et al, 2017).…”
Section: Discussionunclassified
“…Destaca-se que neste caso não foram encontradas associações significativas com as variáveis de exposição estudadas. Algumas hipóteses sobre as associações com o desfecho são apresentadas em estudos internacionais, como Hall e Sigaúque, os quais sugerem que exames positivos para EGB estejam relacionados ao sistema imunológico materno (HALL et al, 2017;SIGAÚQUE et al, 2018) e possivelmente não apresente associações com variáveis sociodemográficas que consiga caracterizar risco (HADAVAND et al, 2015;MELO et al, 2018).…”
Section: Discussionunclassified